2003
DOI: 10.1016/s0304-3959(03)00039-3
|View full text |Cite
|
Sign up to set email alerts
|

Gut pain and hyperalgesia induced by capsaicin: a human experimental model

Abstract: Human experimental visceral pain models using chemical stimulation are needed for the study of visceral hyperexcitability. Our aim was to stimulate the human gut with chemical activators (capsaicin, glycerol) and measure quantitatively the induced hyperexcitability to painful mechanical gut distension. Ten otherwise healthy subjects with an ileostoma participated. Increasing volumes of capsaicin 50 microg/ml (0.25, 0.5, 0.75, 1.0, 1.5, 2.0, and 3 ml), glycerol (2.5, 5, and 10 ml) or saline (2.5, 5, and 10 ml) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 37 publications
2
80
0
Order By: Relevance
“…The potential role of TRPV1 in integrating different physical, chemical, and inflammatory signals and the comparatively high number of capsaicin-responsive colon sensory neurons support the relevance of this channel in sensation and visceral nociception. Consistent with these considerations, luminal application of capsaicin or capsaicin injection into the gut wall lowers sensory threshold or triggers pain in humans (Drewes et al, 2003;Schmulson et al, 2003;Lee et al, 2004). Interestingly, prolonged administration of red pepper, which contains capsaicin, improved symptoms in patients with functional dyspepsia (Bortolotti et al, 2002), likely because of neurotoxic effects of persistent TRPV1 stimulation that leads to transient analgesia in experimental models of neuropathic or inflammatory pain (Karai et al, 2004).…”
Section: Discussionmentioning
confidence: 91%
“…The potential role of TRPV1 in integrating different physical, chemical, and inflammatory signals and the comparatively high number of capsaicin-responsive colon sensory neurons support the relevance of this channel in sensation and visceral nociception. Consistent with these considerations, luminal application of capsaicin or capsaicin injection into the gut wall lowers sensory threshold or triggers pain in humans (Drewes et al, 2003;Schmulson et al, 2003;Lee et al, 2004). Interestingly, prolonged administration of red pepper, which contains capsaicin, improved symptoms in patients with functional dyspepsia (Bortolotti et al, 2002), likely because of neurotoxic effects of persistent TRPV1 stimulation that leads to transient analgesia in experimental models of neuropathic or inflammatory pain (Karai et al, 2004).…”
Section: Discussionmentioning
confidence: 91%
“…However, dramatic symptom response following capsaicin injection suggests that TRPV1 receptors are indeed present and functional in normal esophageal mucosa and submucosa. Drewes et al 23 demonstrated that capsaicin administration in the ileum (through a stoma) can elicit "burning" and "boring" symptoms. Furthermore, in their studies TRPV1 activation was also found to play a role in the distension-induced visceral hyperalgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in their studies TRPV1 activation was also found to play a role in the distension-induced visceral hyperalgesia. 23,24 Capsaicin is a specific agonist of TRPV1 and has been extensively used to study the mechanism of somatic pain (intradermal junction). 13,14 While the strength of a human experiment, like ours, is that it allows qualitative and quantitative assessment of pain, it does not allow detailed study of the molecular mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…It has been concluded that capsaicin evokes abdominal sensations by stimulation of chemoreceptors and not mechanoreceptors (Schmidt et al, 2004). However, several studies have found reduction in pain thresholds to mechanical, electrical, and thermal stimulation (Gonzalez et al, 1998;Drewes et al, 2003b;Lee et al, 2004;Hammer and Vogelsang, 2007;Olesen et al, 2009;Brock et al, 2010). This indicates that capsaicin must affect a variety of receptors, and sensitization/ desensitization is not necessarily dependent on the quality of receptor activation but more the quantity or duration.…”
Section: Intraesophageal Capsaicin Installationmentioning
confidence: 99%